Disulfiram modulates stemness and metabolism of brain tumor initiating cells in atypical teratoid/rhabdoid tumors. Issue 6 (4th November 2014) - Choi, Seung Ah; Choi, Jung Won; Wang, Kyu-Chang; Phi, Ji Hoon; Lee, Ji Yeoun; Park, Kyung Duk; Eum, Dayoung; Park, Sung-Hye; Kim, Il Han; Kim, Seung-Ki
Abstract: Background: Atypical teratoid/rhabdoid tumors (AT/RT) are among the most malignant pediatric brain tumors. Cells from brain tumors with high aldehyde dehydrogenase (ALDH) activity have a number of characteristics that are similar to brain tumor initiating cells (BTICs). This study aimed to evaluate the therapeutic potential of ALDH inhibition using disulfiram (DSF) against BTICs from AT/RT. Methods: Primary cultured BTICs from AT/RT were stained with Aldefluor and isolated by fluorescence activated cell sorting. The therapeutic effect of DSF against BTICs from AT/RT was confirmed in vitro and in vivo. Results: AT/RT cells displayed a high expression of ALDH. DSF demonstrated a more potent cytotoxic effect on ALDH + AT/RT cells compared with standard anticancer agents. Notably, treatment with DSF did not have a considerable effect on normal neural stem cells or fibroblasts. DSF significantly inhibited the ALDH enzyme activity of AT/RT cells. DSF decreased self-renewal ability, cell viability, and proliferation potential and induced apoptosis and cell cycle arrest in ALDH + AT/RT cells. Importantly, DSF reduced the metabolism of ALDH + AT/RT cells by increasing the nicotinamide adenine dinucleotide ratio of NAD + /NADH and regulating Silent mating type Information Regulator 2 homolog 1 (SIRT1), nuclear factor-kappaB, Lin28A/B, and miRNA let-7g. Animals in the DSF-treated group demonstrated a reduction of tumor volume ( P < .05) and a significant survival benefit ( P = .02). Conclusion: Our study demonstrated the therapeutic potential of DSF against BTICs from AT/RT and suggested the possibility of ALDH inhibition for clinical application.